Effect of Organic Mulching on Soil Moisture, Yield, and Yield Contributing Components of Sesame (Sesamum indicum L.) - Goitom Teame; Alemtsahay Tsegay; Berhanu Abrha (International Journal of Agronomy)
Sesame (Sesamum indicum L.) is one of the chief foreign exchange earning oil crops in Ethiopia. However, its productivity remains low due to lack of appropriate agronomic practices. The aim of this research was to study the effect of organic mulches on sesame productivity and in situ moisture conservation. This experiment was carried out in Humera Agricultural Research Center, Western Tigray, during 2015 growing season. The experimental design was Randomized Complete Block Design with three replications. There were four types of organic mulches; rice straw, sorghum straw, sesame straw, and Sudan grass were compared with control. Sesame, variety Setit-1 was used in the experiment. The organic mulching rate of application was 10 ton ha−1 and this was applied evenly to the soil immediately after germination. Soil water content, phonological characteristics yield, and yield components of sesame were collected. The analyzed results indicated that organic mulching had significant effect on soil moisture content at 0–0.2 m, 0.21–0.4 m, and 0.41–0.6 m in every two-week interval after sowing and grain yield of sesame. Sesame straw conserved highest soil moisture content as compared with respective mulch material. The highest yield (664 kg ha−1) was recorded with Sudan grass while the lowest grain yield (190 kg ha−1) was recorded with no mulch.